THE EFFECT OF SILKWORM PUPAE (Bombyx mori) MEAL TO SUBSTITUTE FISH MEAL ON PRODUCTION AND PHYSICAL QUALITY OF QUAIL EGGS (Cortunix cortunix japonica) - Rahmasari, R.; Sumiati, S.; Astuti, D. A. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The aims of this study was to determine the effect of substitution of fish meal protein withsilkworm pupae (Bombyx mori) on quail performances and egg quality. The experiment was a completlyrandomized design (CDR) with four treatments and four replications and ten birds of each replication.The treatment diets were R0: diet contain 8% fish meal, without silkworm pupae (control), R1: dietcontain silkworm pupae subtituted of 25% fish meal protein, R2: diet contain silkworm pupae subtitutedof 50% fish meal, protein and R3: diet contain silkworm pupae subtituted of 75% fish meal protein. Theresults showed that substitution of 25% up to 75% significantly (P<0.05) reduced feed conversion ratio,significantly (P<0.05) increased egg production and did not affecting physical quality of quail eggs. Inconclusion, silkworm pupae can be used 25% up to 75% replacing protein fish meal.